Queer festivals : challenging collective identities in a transnational Europe - Eleftheriadis, Konstantinos (Protest and social movements ;, 2018)
Is queer really anti-identitarian? And how is it experienced at the European level? At queer festivals, activists, artists and participants come together to build new forms of sociability and practice their ideals through anti-binary and inclusive idioms of gender and sexuality. These ideals are moreover channeled through a series of organizational and cultural practices that aim at the emergence of queer as a collective identity. Through the study of festivals in Amsterdam, Berlin, Rome, Copenhagen, and Oslo, this book thoughtfully analyzes the role of activist practices in the building of collective identities for social movement studies as well as the role of festivals as significant repertoires of collective action and sites of identitarian explorations in contemporary Europe.